Questioning scientific practice: linking beliefs about scientists, science agencies, and climate change. Issue 2 (2nd April 2020) - Safford, Thomas G.; Whitmore, Emily H.; Hamilton, Lawrence C.
ABSTRACT: The climate-change debate in the U.S. has increasingly turned from discussing climate data and scientific consensus to questioning the credibility of scientists. While disinterested unbiased assessment of data is a fundamental norm within the scientific community, it is unclear whether the public believes scientists are objective in their practices or how general views about scientists' integrity shape acceptance of climate-related scientific claims. Using a nationwide survey dataset, we find that many Americans think scientists adjust their findings to get the answers they want, and those who question scientists' objectivity are significantly less likely to trust climate science agencies for information or to accept climate-related scientific facts. Applying generalized structural equation modeling to our data, we show the importance of both the direct effects of individual perceptions of scientists' objectivity on beliefs about climate change, and indirect effects through their influence on levels of trust in scientific agencies providing climate data. Our results suggest that the scientific community may need to expand discussion of the ethics and rigor of their practices when discussing climate change and point to the importance of further sociological investigation of how perceptions of scientists and scientific practices shape climate views.